The Paris Climate Agreement: what it means for food and farming - Meadu, Vanessa; Coche I; Vermeulen, Sonja J.; Friis, Anette Engelund (2015)
The Paris Agreement opens the door for more adaptation and mitigation in the agriculture sector. Countries must take urgent action to reduce emissions from the agriculture sector in order to limit global warming below 2 degrees C. Funding and political will are needed to support developing countries to implement their plans to combat and adapt to climate change in the agriculture sector. The global agriculture community, including CGIAR, must step up and engage in key UNFCCC processes between now and 2020 to drive action and innovation on issues related to agriculture